(untitled) (Bangladesh Journal of Medical Biochemistry, 2023)
Type 2 diabetes mellitus is a chronic disease characterized by relative or absolute deficiency of insulin, resulting in glucose intolerance. The prevalence of diabetes is rapidly rising all over the globe at an alarming rate. Hyperuricemia is probably associated with glucose intolerance due to various mechanisms, however, the most important is the association between insulin and renal resistance to absorption of urates. 1/2, The aim of the study is to examine the serum uric acid level in Type 2 male Diabetic patients and to assess the association of serum uric acid level with fasting blood sugar (FBS), blood sugar two hours after breakfast (2HAB), glycated hemoglobin (HbA1C), duration of diabetes, and exercise time. This case-control study was conducted in Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM), out-patient department (OPD) during the period of June 2016 to January 2017. It included 110 Subjects of type 2 male diabetic patients as cases. In addition 100 age and sex matched non-diabetic male subjects were randomly selected as control Results: The mean serum uric acid of all cases of Type 2 DM was 8.39±2.61mg/dl which was significantly higher than controls (5.14±84 mg/dl). The study found that there were significant differences in mean age, duration of diabetes, exercise time, waist-hip ratio, systolic blood pressure (SBP), and diastolic blood pressure (DBP) within cases and controls but no significant differences of mean BMI was found. This study also found that significant differences in mean of FBS, ABF and HbA1C between case and controls but there was no significant differences of mean TG, Cholesterol, HDL and LDL. The serum uric acid was not significantly correlated with FBS, 2HAB and HbA1C but significantly correlated with exercise time where r =.340. Chi square test was carried out to measure the association between HbA1C and Uric acid category. But had no significant association Conclusion: Our study findings conclude that serum uric acid is not significantly correlated with FBS, 2HAB and HbA1C, but significantly correlated with age, duration of DM, and exercise time. Bangladesh J Med Biochem 2018; 11(2): 11-16